Effective cooperation with energy consumers: An example of an ethical approach to introduce an innovative solution. Issue 2 (6th May 2014) - Begier, Barbara
Abstract : Purpose: – Research described in this paper focuses on a need to consult inhabitants about a new technical solution introduced in a country-wide scale like it is in the case of a smart metering system – finally, all energy consumers will become its users. Its social acceptance is required. So it is a good example of an ethical approach to introduce an innovative solution in the society. The conducted research was intended to help developing strategy to build appropriate relationships with energy consumers during the planned exchange of energy meters and to prepare energy consumers to make use of all functionality of the installed meters. The course of the conducted research and its results are presented. The paper aims to discuss these issues. Design/methodology/approach: – The described forms of cooperation with people are direct interviews in focus groups and a questionnaire survey involving representative social sample (surveys have been conducted during direct meetings and via internet). They are described as a case study. An agenda of each interview and also a content of a questionnaire cover topics within the area of natural environment protection, a need to save energy, individual activities leading to energy saving, smart metering, its benefits and potential threats including risk of intrusion privacy. Selected results are included. Findings: – Consultations (with energy consumers) based on focus groups and questionnaire surveys have been well accepted by the participants. Respondents feel a need to express their opinions on a given subject. Citizens' attention concerns mostly the economic aspects of a new system. Energy consumers are able to formulate and declare strong and weak points of smart meters. Some threats concerning intrusion of privacy have been expressed by respondents and included in the paper. Practical implications: – General conclusion is the following – each large system is not only a set of technical devices and software routines but it is also a system built by humans and for humans. Wide consultations on a smart metering bring benefits and help ensuring social acceptance. The raising social awareness of the need to save energy is one more benefit from the undertaken activities. An importance of consulting people about new solution involving all inhabitants is emphasized. Direct and structured interviews are the preferred form of social consultations. it is highlighted by some of the pollsters involved in the survey that respondents tell the truth rather in a direct conversation than in a remote mode via internet (involved pollsters have had an opportunity to check if respondents' statements are true). Originality/value: – The described research took place in November 2012. Earlier only technical experts and academia were involved in discussions concerning smart metering. Selected data are included to show results of the research. The presented approach may help interested parties to introduce new solution and to avoid social opposition, rejection of the idea and misunderstandings.